Kinesiophobia and self‐management behaviour related to physical activity in Chinese patients with coronary heart disease: The mediating role of self‐efficacy. Issue 1 (30th June 2022) - Zhang, Siai; Wang, Zhangyi; Lin, Xinyu; Li, Yawen; Xue, Yuanyuan; Ban, Junkun; Li, Ge; Fa, Tiane
Abstract: Aim: The purpose of this study was to explore the relationship among kinesiophobia, self‐efficacy and self‐management behaviour related to physical activity (SMBPA) in Chinese patients with coronary heart disease(CHD) and the mediating role of self‐efficacy between kinesiophobia and SMBPA in Chinese patients with CHD. Design: A cross‐sectional study. Methods: From March to July 2021, 540 Chinese patients with CHD were investigated with three scales using convenient sampling method. The data were analysed with Pearson correlation, univariate analysis, multivariate linear regression and the PROCESS macro. Results: 509 valid questionnaires were collected (effective response rate: 94.2%). Low kinesiophobia and high self‐efficacy were related to high‐levels of SMBPA (all p < .01). Besides, the effect of kinesiophobia on SMBPA was partially mediated by self‐efficacy, and the mediation effect accounted for 35.59% of the total effect.